Education in Values: Responsibility of Law School? - Boza Dibos, Beatriz (2009)
This paper addresses the professional responsibility in the training of lawyers and the implication of the existence of values in the practice of their profession. The authors recognize that lawyers act observing principles and duties; therefore, their performance is not limited to the defense of their clients but is linked to the defense of people's rights and the consolidation of the Constitutional Rule of Law, justice and social order. Likewise, the authors analyze the influence of the introduction of values in the training of lawyers, as well as the attitudes developed by students and professors regarding their professional performance. Finally, they present a proposal regarding the theoretical-practical approach to training in the Law School called "systemic model for training in values".